China's New Public Diplomacy Implementation Using Vaccines in the Covid-19Pandemic Era - Wahyudi, Stevany Putri; Prinanda, Devita (Universitas Muhammadiyah Malang, 2023)
This article analyzes the implementation of New Public Diplomacy using the covid-19 vaccine by the Chinese government. In answering the problem, this article applies a qualitative descriptive method. The data source is used in the form of literature, which includes journals, books, reports, news articles, and other sources accredited by Sinta or ISSN and related to the research topic. Researchers obtain literature sources in the form of scientific works through the Harzing Publish or Perish application, and other data sources come from Google. In analyzing the discussion results, the author uses the concept of New Public Diplomacy initiated by Jan Melissen. This research is interesting to study because China responded to the global public's bullying regarding accusations of negligence as the cause of the Covid-19 pandemic by getting up and restoring its image, namely by supplying vaccines to several countries. The results of this study show that China is using the Belt Road Initiatives' commitment to the Health Silk Road program as their Nation-Branding and China are capable of being adaptive in carrying out New Public Diplomacy. However, China failed to ensure the public because the public had suspicions about China's hidden motives.